Instruction Teaching Support System and Teaching Competency in Applied Colleges , China - Ma, Cuifeng; Casihan, Maria Luvimi l. (Pacific International Journal, 2024)
This research examines the effectiveness of the Instruction Teaching Support System and Teaching Competency in Applied Colleges in China, surveying 303 teachers and 381 students using a quantitative approach. The findings reveal that the school's teaching support initiatives have effectively addressed teachers' needs for professional development, contributing positively to their teaching practices and career growth. Teachers expressed high satisfaction with the support system, noting its positive impact on daily teaching and career advancement. The management system was seen as well-organized, with clear development pathways and strong institutional backing for improving teaching quality. The school's performance incentives, such as merit-based pay, promotions, and welfare benefits, were widely appreciated for motivating teachers. Teachers also valued the diverse skills training opportunities provided by the school, which helped them adapt to modern educational demands. Students also rated their teachers highly, particularly in terms of professionalism, ethical conduct, and assessment abilities, indicating the positive influence of the school's support system on teaching competency. Overall, the study concludes that a well-structured teaching support system is crucial for fostering teachers' professional growth and enhancing teaching quality.